2012
DOI: 10.1007/s11606-011-1952-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Hepatocellular Carcinoma Surveillance Among American Patients: A Systematic Review

Abstract: BACKGROUND: Although surveillance for hepatocellular carcinoma (HCC) is recommended in high-risk patients, several studies have suggested it is being underutilized in clinical practice. The aim of our study was to quantify utilization rates for HCC surveillance among patients with cirrhosis and summarize patterns of association between utilization rates and patient socio-demographic characteristics. DATA SOURCES: We performed a systematic literature review using the Medline database from January 1990 through M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
224
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 249 publications
(241 citation statements)
references
References 26 publications
12
224
3
2
Order By: Relevance
“…29 However, underutilization of HCC surveillance is common with most studies reporting rates below 30%. 30 Similar situation may also occur in kidney transplant recipients. In our cohort, only 4 out of the 20 patients diagnosed with HCC received USG surveillance at intervals between 6 and 12 months.…”
Section: Discussionmentioning
confidence: 82%
“…29 However, underutilization of HCC surveillance is common with most studies reporting rates below 30%. 30 Similar situation may also occur in kidney transplant recipients. In our cohort, only 4 out of the 20 patients diagnosed with HCC received USG surveillance at intervals between 6 and 12 months.…”
Section: Discussionmentioning
confidence: 82%
“…Several cohort studies have demonstrated that HCC surveillance is associated with higher rates of early tumor detection, curative treatment receipt, and overall survival (6) ; however, fewer than 20% of patients with cirrhosis in the United States undergo HCC surveillance. (7) HCC surveillance rates are even lower among racial-ethnic minorities and patients of low socioeconomic status (SES), likely related to a combination of medical, socioeconomic, and cultural issues. (8) Although provider recommendation is reported to be a strong predictor for HCC surveillance, (9) patient-level factors may also play an important role in surveillance underuse.…”
Section: Conclusion-patientsmentioning
confidence: 99%
“…(12,13) However, most studies evaluating HCC surveillance correlates have primarily focused on patient sociodemographic and clinical characteristics. (7,14) The effect of theory-based, patient-reported psychosocial factors on HCC surveillance completion has not been quantified. A better understanding of patient knowledge, attitudes, and barriers, particularly among low-income minorities, is crucial to develop and implement effective interventions to improve HCC surveillance rates.…”
mentioning
confidence: 99%
“…Similarly, among patients in the national VA Hepatitis C Clinical Case Registry, black patients were less likely than any other racial group to undergo routine surveillance (OR 0.6, 95% CI=0.45-0.81) defined as either AFP or ultrasound in two consecutive years within the first four years after diagnosis of cirrhosis [41].…”
Section: Lower Hcc Surveillance Rates In African Americansmentioning
confidence: 99%